Movement behaviour and fishery interaction of silky sharks (Carcharhinus falciformis) in the tropical tuna purse seine fishery in the Western Indian Ocean. (21st June 2021) - Filmalter, John D; Bauer, Robert K; Forget, Fabien; Cowley, Paul D; Dagorn, Laurent
Abstract: The silky shark Carcharhinus falciformis regularly associates with floating objects in the open ocean, resulting in relatively high levels of bycatch in industrial tuna purse seine fisheries using drifting fish aggregating devices (FADs). This bycatch has contributed to concerns regarding the sustainability of this fishery and its impact on silky shark populations. To investigate fishery interactions, movements of 28 silky sharks (86–235 cm TL, mean = 118 cm) fitted with pop-up and archival tags in the western Indian Ocean, between 2010 and 2012, were examined. Monthly overlap between probability surfaces of sharks and two fishery metrics (FAD-tuna catches and FAD positions) were calculated. Vertical habitat use overlapped almost entirely with operational gear depth. Horizontal movements were extensive (3–5024 km) and covered large areas of the western Indian Ocean. Monthly overlap with FAD distributions was consistently high (64.03–100%) highlighting the need for compliance with FAD design regulations to avoid entanglement. Monthly overlap with tuna catches was more variable (8.43–51.83%). The observed movement patterns suggest static spatial management measures would be have limited conservation impact, however dynamic approaches could be appropriate. Limiting fishery activities directly will likely have the greatest conservation outcomes for silky sharks in the purse seine fishery.